Study on Different AKIS Actors on Agricultural Knowledge and Information Dissemination - Golam Torab Ali; Ganesh Das; Litan Das; Sabita Mondal; Prabhat Kumar Pal; Ashutosh Sarkar; Deb Sankar Gupta (Archives of Current Research International, 2024)
The study on the Agricultural Knowledge Information System (AKIS) in the Jalpaiguri District of West Bengal (2017-2023) aimed to understand the actors involved and their inter-linkages for disseminating agricultural knowledge and information. It focused on three blocks: Jalpaiguri Sadar, Maynaguri, and Dhupguri. The findings indicated a high linkage diversity (average value of 0.79), suggesting a dense network of connections among actors. However, the linkage strength was weak (average value of 0.15), highlighting that while a broad network of interactions exists, the effectiveness of these connections needs improvement. Despite challenges in mobilizing officials for data collection, the study provided valuable insights into the AKIS in the district.